Simulation and experiment research on heat treatment of micro and nano BN particles modified casting aluminum copper alloys - Rong Li; Chao Zhou; Ziqi Zhang; Xiaohong Ji; Xin Liu; Quan Wu; Lixia Wang; Qi Zeng (Scientific Reports)
Abstract The heat treatment process is a key technology to improve the performance of cast aluminum-copper alloys with micro-nano boron nitride (BN) particles, but its strengthening mechanism still needs to be studied. Orthogonal tests were used to carry out heat treatment experiments on aluminum matrix ceramic composites prepared by adding different contents of micro-nano BN particles. Then, a crystal model was established, and the heat treatment process was simulated by the molecular dynamics (MD) method. The heat treatment results show that the mechanical strength and elongation of the nano-BN/aluminum matrix composites with a content of “2%” are significantly increased (9.52% and 23.28%) after heat treatment with a solution temperature of 545 °C, a solution duration of 9 h, an aging temperature of 150 °C and an aging of 8 h. The stress calculation results based on MD are also consistent with the experimental conclusions. The results of microstructure and MD calculations show that the micro/nano BN particles would promote the rearrangement of the lattice and make other lattice types transform to the hexagonal close-packed (HCP) phase during heat treatment, which would be enforced the grain boundaries of the alloy, hindered the movement and diffusion of dislocations, reduced the formation of dislocation defect surfaces, and improved the tensile strength and hardness of the alloy. At the same time, the recrystallization of heat treatment causes the dislocations to undergo cross-slip and lattice rotation in the process of plane slip, resulting in the annihilation of multiple groups of dislocations due to interaction, which makes the plasticity of the material slightly decrease. The coexistence of the residual face-centered cubic phase and the HCP phase in the internal structure makes the composite material have a good balance of strength, hardness and ductility.